A Note on the Drazin Indices of Square Matrices - Lijun Yu; Tianyi Bu; Jiang Zhou (The Scientific World Journal)
For a square matrix A, the smallest nonnegative integer k such that rank (Ak) = rank (Ak+1) is called the Drazin index of A. In this paper, we give some results on the Drazin indices of sum and product of square matrices.